Therapeutic Efficacy of Anti-Bestrophin Antibodies against Experimental Filariasis: Immunological, Immune-Informatics and Immune Simulation Investigations - Nabarun Chandra Das; Anindya Sundar Ray; Jagadeesh Bayry; Suprabhat Mukherjeee (Antibodies, 2021)
Lymphatic filariasis (LF) is a debilitating parasitic disease caused by filarial parasites and it is prevalent across the underprivileged population throughout the globe. The inadequate efficacy of the existing treatment options has provoked the conception of alternative strategies, among which immunotherapy is steadily emerging as a promising option. Herein, we demonstrate the efficacy of an antibody-based immunotherapeutic approach in an experimental model of filariasis, i.e., Wistar rat infected with Setaria cervi (a model filarial parasite). The polyclonal antibodies were raised against filarial surface antigen bestrophin protein (FSAg) in mice using the purified Wuchereria bancrofti FSAg. The adoptive transfer of anti-FSAg antibody-containing serum resulted in the significant reduction of parasite burden in filaria-infected rats. Intriguingly, anti-FSAg sera-treated animals also displayed a reduction in the level of proinflammatory cytokines as compared to the infected but untreated group. Furthermore, our in silico immunoinformatics data revealed eight B-cell epitopes and several T-cell epitopes in FSAg and these epitopes were linked to form a refined antigen in silico. The immune simulation suggested IgM and IgG1 as the predominant immunoglobulins induced in response to FSAg. Taken together, our experimental and simulation data collectively indicated a therapeutic potential of anti-FSAg sera against LF.